Data "WAAM of a complex superalloy component" - James, William Sean; Pardal, Goncalo; Ganguly, Supriyo (Cranfield University, 2025)
Wire Arc Additive Manufacturing complex Inconel 718 superalloy component. Research explored the feasibility of additively manufacturing superalloy components for high-speed flight and methods to enhance the performance of Wire Arc AM superalloy components.
Time-lapse video
Keywords: WAAM; superalloy; Inconel 718